2013
DOI: 10.1108/09534811311328588
|View full text |Cite
|
Sign up to set email alerts
|

Organizational change and psychological reactance

Abstract: PurposeThe purpose of this paper is to focus on the resistance to change in the organizational contexts where a soon‐to‐be‐implemented change initiative infringes upon freedoms of the employees. Specifically, the role of affect was explored within the framework of psychological reactance theory, delineating salience of affect as a driver of the intention to restore one's threatened freedoms. Additionally, the roles that emotional intelligence and interpersonal justice play in lowering the activation of reactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 123 publications
(178 reference statements)
2
33
1
Order By: Relevance
“…Due to globalization and stiff competition, change becomes necessary for organizations, and every change faces CC from all quarters [16,96]. Basically, CC is aroused because of discomfort resulting from the expected change [16,20,96,97]. Boomer et al [98] suggested that CC has detrimental effects on prospective change.…”
Section: Organizational Change Cynicismmentioning
confidence: 99%
“…Due to globalization and stiff competition, change becomes necessary for organizations, and every change faces CC from all quarters [16,96]. Basically, CC is aroused because of discomfort resulting from the expected change [16,20,96,97]. Boomer et al [98] suggested that CC has detrimental effects on prospective change.…”
Section: Organizational Change Cynicismmentioning
confidence: 99%
“…Furthermore, they may satisfy three basic employee needs, as offered by the self-determination theory: (a) an emotionally intelligent manager's excellent interpersonal skills, such as empathy, affirms employee expressions of individuality (satisfying the need to be autonomous); (b) work-unit cohesion, shaped by an emotionally intelligent manager, appeals to the employee's need to belong; and (c) socio-emotionally well-channeled sales-directed behaviors enable an employee to satisfy the need to feel competent (Kovjanic, Schuh, Jonas, Van Quaquebeke, & Van Dick, 2012). Future combinations of selfdetermination and EI research, such as that of Nesterkin (2014) and of Perreault, Mask, Morgan, and Blanchard (2014), could extend these ideas, including the shown resource caravan or chain reactions reported herein.…”
Section: Discussionmentioning
confidence: 95%
“…Secondly, organizational justice [10] is also adopted to evaluate the hospital practice in equality of distributive, procedural, interpersonal, and informational justice. Besides, psychological reactance theory suggests that one unfavorable feeling will result in negative behaviors such as resistance behaviors [11]. Wetherefore infer that healthcare professionals expect to be treated equally when adopting the EMRs to the working place.If the hospital fails to do so, an unfavorable perception will be generated, such as perceived contract breach (PCB), leading to resistance behaviors to the EMR adoption work.…”
mentioning
confidence: 91%